Clinical Evidence Based Nursing (EBNP) Penggunaan Berg Balance Scale Untuk Mengkaji Keseimbangan Pada Pasien Stroke - Dwi Kartika Rahayuningtyas; Ratna Sitorus; I Made Kariasa; Yunisar Gultom (Poltekkes Kemenkes Jakarta III, 2021)
Stroke can affect balance. Balance is the ability to maintain the body in a balanced position both in static and dynamic conditions. However, the assessment of the existing balance is only done in a static state in stroke patients. The balance assessment describes the balance of stroke patients so that they can be written on asessment form and the transfer record and can determine the need for balance training as one of the rehabilitation of stroke patients. This EBN application aims to find out the use of Berg Balance Scale to assess the balance of both static and dynamic conditions in stroke patients. The method used is conducting PICO analysis, searching database, critical appraisal, and determining relevant journals. EBN implementation was carried out on 10 people who had a stroke in zone A on the 5th floor of Building A RSUPN Dr. Cipto Mangunkusumo. This study uses the Berg Balance Scale scale in Indonesian. The analysis showed that stroke patients who experienced balance disorders were 7 people and did not experience a balance of 3 people BBS can assess the balance of stroke patients in accordance with existing evidence. BBS can be used as a balance assessment in stroke patients.